MODEL PENDIDIKAN KARAKTER BERBASIS PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH ATAS - Basril, Basril (JURNAL ISLAMIKA, 2023)
Islamic religious education as one of the mandatory curricula in each educational unit is often a black goat due to the behavior of students, because some parties consider that the formation of character and moral development of students are only produced from the output of Islamic religious education. Therefore, this study aims to reveal how the implementation of character education through Islamic religious education. The research was conducted using qualitative methods, the data sources were the principal, vice principal and several purposively selected students. The results of the study are: first, the content of character values in Islamic religious education includes 18 (eighteen) characters. Islamic religious education teachers do not have a complete understanding related to the types of characters contained in Islamic religious education. The model offered is the interconnection of character values with Islamic religious education materials taught in high schools.